Mesenchymal stem cells can improve discogenic pain in patients with intervertebral disc degeneration: a systematic review and meta-analysis - Zhang, Wupeng; Wang, Daofeng; Li, Hua; Xu, Gaoxiang; Zhang, Hao; Xu, Cheng; Li, Jiantao (Frontiers in Bioengineering and Biotechnology, 2023)
Background The meta-analysis aimed to estimate the efficacy of mesenchymal stem cells (MSC) on lumbar discogenic pain in patients with intervertebral disc (IVD) degeneration. Methods A comprehensive literature search was conducted in the PubMed, Web of Science, Embase and Cochrane Library databases with predetermined search strategy up to September 18, 2022. The clinical studies focusing on evaluating the efficacy and safety of MSCs in patients with intervertebral disc (IVD) degeneration were identified. The primary outcomes were changes of pain score and Oswestry Disability Index (ODI). The Newcastle-Ottawa Scale for cohort studies was used for quality assessment. Review Manager was used to conduct the statistical analysis. Pooled risk ratios (RRs) were calculated based on the random effect model. Heterogeneity, subgroup, and publication bias analyses were also performed. Results There were 2392 studies were identified in the initial search, and 9 eligible studies with 245 patients were eventually included in this review. The Visual Analogue Scale (VAS) score was significantly lower in patients after receiving MSC therapy (mean difference = 41.76; 95% confidence interval [CI] 25.20 to 58.31; P < 0.001; Heterogeneity: I2 = 98%; P < 0.001). And the pooled mean difference of ODI was 22.04 from baseline to final follow up points (95% confidence interval [CI] 8.75 to 35.33; P=0.001; Heterogeneity: I2 = 98%; P < 0.001). The pooled reoperation proportion was 0.074 (95% confidence interval [CI] 0.009 to 0.175; Heterogeneity: I2 = 72%; P < 0.01). There were no serious related adverse events associated with the therapy. Conclusion The findings of this meta-analysis indicated that mesenchymal stem cells therapy may be effective in relieving pain and improving Oswestry Disability Index significantly in patients with lumbar discogenic pain. MSC therapy may also be associated with a lower risk of adverse events and reoperation rates.